Civil engineering topics. proceedings of the 29th IMAC, a conference on structural dynamics, 2011 - Proulx, Tom (Thomas William) (Conference Proceedings of the Society for Experimental Mechanics Series, 2011)
This is the fourth volume of the Proceedings of the 29th IMAC, A Conference on Structural Dynamics, 2011. Civil Engineering Topics, Volume 4 Proceedings of the 29th IMAC, A Conference and Exposition on Structural Dynamics, 2011, the fourth volume of six from the Conference, brings together 35 contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Civil Engineering, including Operational Modal Analysis, Dynamic Behaviors and Structural Health Monitoring.